The Computational Thinking in Elementary School in the Indonesia New Curriculum: A Teacher's Perspective - Zaenal Abidin; Tatang Herman; Wahyudin Wahyudin (Universitas Negeri Malang, 2023)
In the 21st century, thinking is a very important ability, one of which is computational thinking. The purpose of this research is to explain a teacher’s perspective on computational thinking (CT) in elementary school in the Indonesian New Curriculum. The qualitative method was used with a case study. The participant is Bandung's fourth-grade teacher. All teachers received questionnaires. A number of teachers were interviewed. Researchers use data collection tools as their primary tools. The supporting instruments are documentation studies, interviews, and field notes. The results show that teachers know about CT but are still confused about how to teach it in elementary school. They agree that CT is one of the most important skills in the 21st century. They do not understand all CT indicators, and they are unable to formulate CT queries or connect CT with technology. There should be training for teachers on how to integrate learning, technology, and CT.